MORAL VALUES AND FIGURATIVE LANGUAGES IN COLDPLAY’S BAND SONGS - Ripki Pratama; Muhammad Fadjri (Indonesian Publication Center, 2020)
This thesis entitled “Moral Values And Figurative Languages in Coldplay’s Band Songs. Formalis theory and Affective theory are used in analyzing the moral values and figurative languages. Theory that used to image moral values is Formalist theory and theory that used to analysis figurative is Affective thoery. Then, data analyzed by using descriptive analysis method. The result of this study is there are several moral values that found in coldplays song such as regiousity, love, humbleness, peace loving. Figurative languages found are methapor, similie, personification, irony, and symbol in lyrics.